Yield and oil quality of groundnut (Arachis hypogaea L.) genotypes under elevated temperature and carbon dioxide: Yield and oil quality of groundnut (Arachis hypogaea L.) genotypes under elevated temperature and carbon dioxide - M VANAJA; N JYOTHI LAKSHMI; S K YADAV; P SATHISH; C H MOHAN; B SARKAR; M SRINIVASA RAO; M PRABHAKAR; M MAHESWARI; G RAVINDRA CHARY (Journal of Oilseeds Research, 2020)
The biomass and seed yield of groundnut (Arachis hypogaea L.) genotypes were affected by elevated temperature of +3°C (eT) and the presence of elevated CO2 of 550 ppm (eT+eCO2) ameliorated these impacts to some extent. K-6 and Narayani are sensitive to high temperature and responsive to eCO2 and K-9 showed better tolerance to higher temperature (>40°C). The eT and eT+eCO2 conditions significantly altered the oil content, saturated and unsaturated fatty acid levels of groundnut genotypes.